Izseljenski tisk v Ameriki v digitalni dobi - Pogačar, Timothy (Slavistična revija, 2017)
The Slovene-American newspaper Prosveta has been published by the Slovene National Benefit Society (Slovenska narodna podporna jednota) since 1908. Historically, literature and essays occupied a prominent place in the paper, along with organizational news from around the United States. In 1999, the newspaper began digital production and became available in both digital and print forms. Since 2001, the print edition changed from weekly to biweekly and later to monthly. This study will examine the impact of digital production and distribution on Prosveta's contents over the past fifteen years and on its distribution over the past five years. It will include comparisons to the distribution of similar newspapers in the U. S.
Keywords: 20.-21. st.; časopisje; distribucija; elektronski mediji; produkcija; Prosveta; slovenski izseljenci; tiskani mediji; United States of America; ZDA